2019
DOI: 10.1037/rel0000192
|View full text |Cite
|
Sign up to set email alerts
|

Can Abraham bring peace? The relationship between acknowledging shared religious roots and intergroup conflict.

Abstract: Although the protracted Israeli-Palestinian conflict is rooted in contesting ethno-national narratives, it is often also framed and perceived in religious terms. While all three groups who consider the region a holy land, namely Jews, Muslims and Christians, have theological roots in common, the potential of emphasizing such commonalities among more than two groups and-most importantly-whether acknowledging such shared Abrahamic lineage generally may be an asset for actual peacemaking in the region remains unk… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…Across three experiments, using various workplace scenarios, atheist employees faced more obstacles than Christian, Jewish, or Muslim employees when requesting belief-relevant accommodations at work. These findings are consistent with the common ingroup identity model (Gaertner & Dovidio, 2014), which suggests that atheists are stigmatized and considered an outgroup to a greater extent than even many religious minorities (e.g., Jews, Muslims); such minorities at least share Abrahamic traditions with the religious majority (Christians) (see Kunst et al, 2019). Despite that the effects of participant religiosity varied across studies, a combined analysis of Studies 1-3 (reported in the Supplementary Materials) revealed that overall, religious individuals are least likely to accommodate atheist targets' religion-related workplace requests.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Across three experiments, using various workplace scenarios, atheist employees faced more obstacles than Christian, Jewish, or Muslim employees when requesting belief-relevant accommodations at work. These findings are consistent with the common ingroup identity model (Gaertner & Dovidio, 2014), which suggests that atheists are stigmatized and considered an outgroup to a greater extent than even many religious minorities (e.g., Jews, Muslims); such minorities at least share Abrahamic traditions with the religious majority (Christians) (see Kunst et al, 2019). Despite that the effects of participant religiosity varied across studies, a combined analysis of Studies 1-3 (reported in the Supplementary Materials) revealed that overall, religious individuals are least likely to accommodate atheist targets' religion-related workplace requests.…”
Section: Discussionsupporting
confidence: 88%
“…The common ingroup identity model might suggest that Christians, Jews, and Muslims comprise a superordinate category “religious,” whereas atheists comprise a separate category altogether and hence should face more discrimination in the workplace compared to not only Christians, but also Jews and Muslims. Supporting this possibility, Christian, Jewish, and Muslim individuals who acknowledge the shared Abrahamic lineage of all three religions—that is, who recognize all three religions as part of the same superordinate group—subsequently exhibit less prejudice against one another (Kunst & Thomsen, 2015; Kunst et al, 2019). Importantly, shared Abrahamic categorization does not affect atheists’ attitudes toward members of religious groups, which further underscores atheists’ status as the outgroup in this context (Kunst & Thomsen, 2015).…”
Section: Anti-atheist Workplace Discriminationmentioning
confidence: 99%
“…Muslims and Christians who endorsed a shared/common Abrahamic group in addition to their own specific religious identities were more positive towards each other than those who did not hold such dual identities (see also Kunst et al, 2018). In this paper, we propose that the residual religious identity may similarly provide a deconvert with a dual identity (e.g., that of "a religious atheist") (cf.…”
Section: Introductionmentioning
confidence: 85%
“…Thus, we hypothesized that in such a conflict, both Muslim Palestinians and Jewish Israelis may predict that their outgroup members' belief in God discourages cooperation in intergroup encounters. Based on prior research and theorizing (Norenzayan, et al, 2016;Kunst et al, 2019), we also reasoned that such perceptions may be particularly likely to the degree that individuals perceive outgroup members to pose a threat to their ingroup and/or if they believe that their ingroup and outgroup do not share a common identity and set of beliefs.…”
Section: Outlier Evidence Of Mutually Positive Intergroup Perceptions...mentioning
confidence: 99%